Bridging the gap: Understanding the link between HR practices and innovative behavior - Gugup Kismono; Vania Olivine Danarilia; Heni Ardianto (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to examine the partial and sequential mediating effects of work engagement (WE) and organizational citizenship behavior (OCB) on the relationship between human resources management practices(HRMP) and innovative work behavior (IWB) to find an integrative relationship mechanism. Design/methodology/approach: This study used a cross-sectional data collection technique to obtain a usable sample of 324 employees in Indonesia who work in the banking sector. The least squares structural equation modeling was applied to the data analysis in this study. Findings: The study's findings suggest that HRMP does not directly influence IWB. However, WE and OCB mediate partially or sequentially in the relationship between HRMP and IWB. These mediating mechanisms shed light on the psychological processes of employees, emphasizing the significance of innovative behavior in the workplace. Research limitations/implications: This research implies the importance of paying attention to the role of WE and OCB in designing and implementing HRMP to increase IWB. These results also highlight the importance of a holistic approach to creating meaning in the workplace that can encourage innovative behavior. Originality/value: This research offers a deeper understanding of the complex relationships between HRMP, WE, OCB, and IWB. These findings explore possible mediating mechanisms previously discovered in the literature and offer new insights for future research in this area.
Keywords: 650; HRM practices; Innovative work behavior; Work engagement; Organizational citizenship behavior; Chain mediation